Experimental study on strain rate effect of strength characteristics of unsaturated silty clay. (June 2020) - Hu, Tianfei; Liu, Dawei; Chang, Jian
Highlights: Effects of strain rate on strength characteristics of subgrade filler were studied. Compression behavior of unsaturated silty clay was investigated in the strain rate range of 5 × 10 −7 ～1 × 10 −3 s −1 through triaxial testing. The intrinsic mechanism of strain rate effect was analyzed considering soil skeleton viscosity, consolidation and pore pressure. Equations describing strain rate effect were derived to facilitate engineering applications. Abstract: Strain rate is a key factor affecting the strength characteristics of soil. The intrinsic mechanism of the strain rate effect was investigated through a case study on unsaturated compacted silty clays, where triaxial tests with elven strain rates and six confining pressures ranging from 5×10 −7 ∼1×10 −3 s −1 and 50∼400 kPa, respectively, were conducted. Then, the effects of strain rate on multiple strength and deformation parameters of the sample, including the stress-strain relationship, failure mode, peak strength, peak strain, and elastic modulus, were analyzed to clarify the inherent mechanism of the strain rate effect. The results showed that there were two types of critical strain rate values, which caused the peak strength to first decrease and then increase with strain rate under low confining pressures. However, under high confining pressures, the peak strength first followed the same trend as low confining pressure, but then it decreased with increased strain rate. Additionally, the elastic modulus increased monotonically with strain rate under low confining pressures, but while under high confining pressures it first decreased and then increased. Finally, linear functions and quadratic polynomials were derived to describe the effect of strain rate on the strength and deformation parameters of silty clay to facilitate engineering applications.